Interaction Of Sympathetic Nervous System And Renin Angiotensin System In Renal Haemodynamics Of Renal Failure, Hypertensive And Renal Failure Hypertensive Rats - Basri, Fathihah (2009)
Adrenoseptor a1 dan reseptor subjenis angiotensinjenis 1 (AT1) memainkan peranan penting dalam pengawalaturan hemodinamik.